Use of AI, Robotics and Modelling Tools to Fight Covid-19. - Jain, Arpit; Sharma, Abhinav; Wang, Jianwu; Ram, Mangey (River Publishers Series in Mathematical and Engineering Sciences, 2021)
This book describes the various AI, IoT, robotics, mathematical and computational modelling tools that have been used to fight the Covid-19 pandemic.